Evaluation of Annual Effective Dose Due to Ingestion in Some Commonly Consumed Vegetables in Lagos State, Nigeria - M. A. Olaoye; T. J. Aluko; J. A. RABIU; O. A. Jegede; O. O. Adeleke (Jordan Journal of Physics, 2025)
The activity concentrations of 40K, 238U and 232Th in some commonly consumed vegetables in Badagry, Ikorodu and Ojo areas of Lagos state were determined. The highest concentration of 40K was obtained in Celosia argentea (Lagos Spinach) with a value of 7807.51±402.48 Bq/kg, the highest concentration of 238U with a value of 59.46±6.46 Bq/kg was found in Amaranthus hybridus (African Spinach) and the highest concentration of 232Th was found in Amaranthus hybridus (African Spinach) with a value of 47.45± 2.80 Bq/kg. The highest concentrations were found in vegetables from Ikorodu. The lowest concentration of 40K was found in Hibiscus sabdariffa (Roselle) with a value of 451.23±23.87 Bq/kg. Celosia argentea (Lagos Spinach) has the lowest concentration value of 0.79±0.10 Bq/kg for 238U and a concentration value of 3.81± 0.22 Bq/kg was found in Vernonia amygdalina (Bitter Leaf) being the lowest concentration value of 232Th. The mean annual effective doses of Badagry, Ikorodu and Ojo were 1.42mSv/y, 2.06mSv/y and 2.23mSv/y, respectively, which were higher than the world mean average of 0.294mSv/y. Keywords: Activity concentration; Vegetables; Mean absorbed dose; Cancer risk.